Satellite-based dgital platform for rice production, and climate impact monitoring for Mali - Mathieu, Renaud; Dossou-Yovo, Eliott; Holecz, Francisco; Murusegan, Deiveegan; Quicho, Emma; Satapathy, Sushree; Akpoffo, Marius; Gatti, Luca (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Rice is a staple crop in Mali, playing a crucial role in the country's economy, food security, and social fabric. It is cultivated in both irrigated and rainfed ecosystems across key rice-growing regions, including Segou, Mopti, Timbuktu, Sikasso, and Selingue. However, despite increasing demand driven by population growth, rice farming in Mali faces significant challenges, particularly climate variability. Effective monitoring of rice production using remote sensing technologies is essential for optimizing yields, improving resource management, and mitigating climate risks. The Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project, in collaboration with national and regional partners, supports climate resilience through climate risk mapping, crop monitoring, and climate impact assessments. Since 2022, IRRI, AfricaRice, and Sarmap have been piloting a digital rice production monitoring platform in Mali, focusing on the Segou/Mopti region (Office du Niger) and Sikasso Circle as part of Phase I. Phase II (2024–2025) aims to scale up and validate the platform nationwide, enhance its performance and adaptation to regional production systems, and integrate it into the national digital information system. This will be achieved through targeted advocacy, institutional interventions, and advanced training. This report outlines the objectives and planned activities for 2024 under the remote sensing-based rice monitoring initiative in Mali, as part of the AICCRA project.